Sifat-sifat kulit perkamen kerbau selama penyimpanan12 minggu dalam kelembaban dan suhu berbeda - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 1993)
The aims of this experiment were to seek 1) the changes in the parchment hide properties of mature male buffalo stored at different humidity and temperature for 12 weeks and 2) stage of humidity and temperature in which the parchment hide properties were still unchanged. Six hides of mature male buffalo were used in this experiment. Eight samples were taken from each back part (butt) of hide, hence the total samples was 48 samples. Twenty-four samples from the left butt were treated in different humidity namely low, moderate and high and stored at 20°C ± 2°C and the other twenty-four from the right butt were stored at 30°C ± 2°C. After 12 weeks of storage, all samples were analysed for their capacity of water absorption and evaporation, bacterial number, pH and chemical composition and physical stength of the parchment hide. The results showed that the treatments did not change significantly on the properties, physical strengthand chemical composition except at high humidity of the buffalo parchment hide.